A Novel Biosorbent, Water-Hyacinth, Uptaking Methylene Blue from Aqueous Solution: Kinetics and Equilibrium Studies. (15th April 2014) - Uddin, Md. Nasir; Islam, Md. Tariqul; Das, Sreejon
Abstract : The adsorption of MB dye from aqueous solution onto HCl acid treated water-hyacinth (H-WH) was investigated by carried out batch sorption experiments. The effect of process parameters such as pH, adsorbent dosage, concentrations and contact time, and ionic strength were studied. Adsorption of MB onto H-WH was found highly pH dependent and ionic strength shows negative impact on MB removal. To predict the biosorption isotherms and to determine the characteristic parameters for process design, Langmuir, Freundlich, Temkin, and Halsey isotherms models were utilized to equilibrium data. The adsorption kinetics was tested for pseudo-first-order (PFO), pseudo-second-order (PSO), intraparticle diffusion (IPD), and Bangham's kinetic models. The Langmuir isotherm model showed the goodness-of-fit among the tested models for equilibrium adsorption of MB over H-WH and indicated the maximum adsorption capacity as 63.30 mg/g. Higher coefficient of determination (R 2 > 0.99 ) and better agreement between the qe (experimental) andq e (calculated) values predicted that PSO kinetic model showed the goodness-of-fit for kinetic data along with rate constant1.66 × 10 - 3, 4.42 × 10 - 3, and3.57 × 10 - 3   mg · g - 1 min ⁡ - 1 / 2 ⁡, respectively, for the studied concentration range. At the initial stage of adsorption, the overall rate of dye uptake was found to be dominated by external mass transfer, and afterwards, it is controlled by IPD mechanism.